10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Objective To identify trends in dental utilization and factors associated with using dental services before and during the pandemic among children with special health care needs (CSHCNs) aged 0 to 17 y. Methods This cross-sectional study analyzed data from the National Survey for Children's Health (NSCH), including a total sample of 78,006 CSHCNs aged 0 to 17 y from 2016 to 2023. Dental utilization trends across the years, including prepandemic and pandemic periods, were analyzed using chi-square tests of independence, while trends stratified by met and unmet dental needs were assessed using the Cochran-Armitage trend test. Pooled multivariable logistic regression analyses were performed to examine the associations between dental utilization and sociodemographic factors. Results CSHCNs were 30% more likely to forgo dental care during the pandemic than in prepandemic years (odds ratio = 1.33; 95% confidence interval, 1.27-1.39). Unmet dental needs, age, household poverty level, caregiver education, caregiver employment, insurance coverage, and race were associated with dental utilization among CSHCNs in pooled regression models and in prepandemic and pandemic regression models. Conclusion This study found lower odds of dental care utilization among CSHCNs during the pandemic. It also demonstrated that factors like unmet dental needs, age, caregiver education, and household poverty level were associated with dental utilization among CSHCNs. Future research should explore the effectiveness of strategies to promote dental care utilization among CSHCNs.Knowledge Transfer Statement:This study found that dental service utilization among CSHCNs significantly decreased during the pandemic compared to prepandemic years. In addition, factors such as unmet dental needs, age, sex, race, caregiver education, insurance coverage, family structure, and household poverty level were associated with dental utilization among CSHCNs. These findings can inform efforts by policymakers to address gaps in access to care and ensure continuity of care, especially during times of instability, such as the COVID-19 pandemic.